The Carthaginian North Semitic influence on early Germanic : a linguistic and cultural study - Mailhammer, Robert, 1975- (North-Western European language evolution. Supplement ;, 2019)
"This book presents a new and innovative theory on the origin of the Germanic languages. This theory presents solutions to four pivotal problems in the history of Germanic with critical implications for cultural history: the origin of the Germanic writing system (the Runic alphabet), the genesis of the Germanic strong verbs, the development of the Germanic word order, and etymologies for key elements of the Germanic lexicon. The book proposes that all four problems can be solved if it is hypothesized that ca. 2,500 years ago the ancestor of all Germanic languages, Proto-Germanic, was in intensive contact with Punic, a Semitic language from the Mediterranean. This scenario is explored by focusing on linguistic data, supported by an interdisciplinary mosaic of evidence. This book is of interest to anyone working on the linguistic and cultural history of the Germanic languages"--